2013
DOI: 10.1093/gastro/got022
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in precision therapy in colorectal cancer

Abstract: Colorectal cancer (CRC) is the most commonly diagnosed cancer in Europe. Because CRC is also a major cause of cancer-related deaths worldwide, a lot of research has been focused on the discovery and development of biomarkers to improve the diagnostic process and to predict treatment outcomes. Up till now only a few biomarkers are recommended by expert panels. Current TNM criteria, however, cause substantial under- and overtreatment of CRC patients. Consequently, there is a growing need for new and efficient bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 205 publications
(239 reference statements)
2
63
0
2
Order By: Relevance
“…It has been proposed previously that p53 expression can be used as a biomarker for prognostic outcomes in cancer patients, though studies are conflicting on its usefulness [34]. Although overexpression is commonly observed in 60-80% of colorectal carcinoma, few studies have shown any statistical significance between p53 overexpression and survival outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed previously that p53 expression can be used as a biomarker for prognostic outcomes in cancer patients, though studies are conflicting on its usefulness [34]. Although overexpression is commonly observed in 60-80% of colorectal carcinoma, few studies have shown any statistical significance between p53 overexpression and survival outcomes [35].…”
Section: Discussionmentioning
confidence: 99%
“…Several known mutations are considered to be associated with a poorer patient outcome and/or failure of response to a certain therapy (18). Patients with inactive TP53 mutations, for example, are at an increased risk of mortality compared with their counterparts, but this mutation does not appear to affect the outcome of chemotherapy (123).…”
Section: Clinical Implication Of the Molecular Genetics Of Crcmentioning
confidence: 99%
“…Although TNM is currently the most common CRC staging system, and an important basis to determine the treatment method and assessing prognosis, it is not a reliable tool for prediction and prognosis. Particularly, CRC patients with similar histopathology may have completely different progression and outcome depending on their genetic and epigenetic background (18). Thus, understanding the molecular pathways underlying the initiation and development of CRC is essential to identify novel molecular biomarkers for diagnosis and prognosis, thereby improving the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies done correlating Ki-67 status and survival rates, it has been found that lower Ki-67 rate was associated with recurrence and lower patient survival. 10 In contrast from the management view, the rapidly proliferating tumours have been found to respond well to adjuvant therapy. The Ki-67 assessment before therapy could predict the effectiveness of the treatment, whereas the same after treatment could predict the disease free survival of patients.…”
Section: Discussionmentioning
confidence: 99%